2002
DOI: 10.1097/00003246-200201000-00023
|View full text |Cite
|
Sign up to set email alerts
|

Marked difference in pathophysiology between tissue factor- and lipopolysaccharide-induced disseminated intravascular coagulation models in rats

Abstract: Because pathophysiology differed remarkably between the tissue factor- and lipopolysaccharide-induced disseminated intravascular coagulation models in rats, we recommend that they be assessed carefully as distinct entities to determine implications of their experimental and clinical use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(30 citation statements)
references
References 21 publications
1
29
0
Order By: Relevance
“…Thus, coagulation protease signaling may sustain a self-amplifying loop through direct and indirect TF induction that continues to drive the inflammatory escalation. Activation of the coagulation cascade by direct infusion of TF results in syndromes of disseminated intravascular coagulation without producing the escalating inflammation that leads to organ damage characteristic of endotoxin challenge (56). Together with the inefficiency of direct thrombin inhibitors (39), these data sup- Figure 2.…”
Section: Tf-dependent Pathways In Alimentioning
confidence: 99%
“…Thus, coagulation protease signaling may sustain a self-amplifying loop through direct and indirect TF induction that continues to drive the inflammatory escalation. Activation of the coagulation cascade by direct infusion of TF results in syndromes of disseminated intravascular coagulation without producing the escalating inflammation that leads to organ damage characteristic of endotoxin challenge (56). Together with the inefficiency of direct thrombin inhibitors (39), these data sup- Figure 2.…”
Section: Tf-dependent Pathways In Alimentioning
confidence: 99%
“…Importantly such suppression of PAI-1 elevation was accompanied with higher concentration of FDP, suggesting that their fibrinolytic activities were improved. Since both animal models 14 and clinical studies 6,24 clearly showed that the enhancement of fibrinolysis is related to better outcome, elevated levels of FDP in the LPS ϩ nafamostat group in the present study suggest their beneficial prognosis.…”
Section: Discussionmentioning
confidence: 49%
“…18 In this paper, we examined whether nafamostat, a broad range protease inhibitor, may improve impaired fibrinolysis in an animal sepsis model. 14 We found that nafamostat attenuated the impairment of fibrinolysis in endotoxemia by suppressing the increase of plasma PAI-1 level.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…with the induced DIC model in rats) indicate that impaired fibrinolysis in conditions of ischaemia is a major pathogenetic factor for organ failure [25], which undoubtedly determines the survival of patients. On the other hand, the observation that our patients with increased levels of D-dimers and PAP were those who died early (group I) testifies to the secondary activation of fibrinolytic processes.…”
Section: Discussionmentioning
confidence: 99%